Mathematics Learning Outcomes and Student Learning Motivation and Teacher Activities in the Integration of Problem Based Learning, Rhealistic Mathematic Education and Snowball Throwing Learning Models - Annisa, Mahmudah Nur; Darmiyati, Darmiyati (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
The problem in this research is the low level of activity, motivation and student learning outcomes in mathematics learning. This is due to the lack of activities that involve students in learning, lack of student motivation and responsibility in learning and difficulty understanding the concept of the material. The aim of this research is to describe teacher activities, analyze student activities, motivation and student learning outcomes. This research method is a combination of qualitative and quantitative approaches, carried out in 3 meetings in the IVA class of SDN Sungai Miai 10 Years in the 2023/2024 academic year with a total of 33 students. Research instruments include teacher activity observation sheets, student activity observations, student learning motivation questionnaires, and student learning outcomes. After that, the data was analyzed descriptively and presented in the form of tables and graphs. From the research results, it can be seen that teacher performance increased at meeting I by 78.12%, II by 84.38%, and III by 93.75% with a rating of "Very Good". Meanwhile, student participation increased at meeting I by 3.03%, II 36.36%, and III 87.88% with the assessment "Almost All Students Are Active". Student learning motivation also increased at meeting I by 3.03%, II 24.24%, and III 93.94%, with the assessment "Almost All Students Are Motivated". Overall, student learning outcomes increased at meeting I by 27.27%, II 48.48%, and III 90.91% with the assessment "Achieved". According to research, it is concluded that the combination of Problem Based Learning, Realistic Mathematic Education, and Snowball Throwing can significantly increase student activity, interest in learning, and achievement.